Novel Quarters for an Odd Couple: Apollo and Dionysis in Beckett's Watt and Pinget's The Inquisitory. - Robert M. Henkels Jr. (Studies in 20th & 21st Century Literature, 1978)
By making the act of writing itself the subject of their works, the French "New Novelists" must face the questions of the source of the creative drive and the possibility of engaging the reader directly in it. The response to these conundrums advanced through example by two of the group's outstanding figures, Samuel Beckett and Robert Pinget, gives a piquant twist to the traditional polarization of artistic impulses into the Apollonian (Reason) and the Dionysian (Unreason). In Watt (1953) and The Inquisitory (1962) writing, the act mitigating life's suffering, springs from the union of these two apparently antithetical drives with the Dionysian elements in the ascendant. Furthermore, the fusion of the seemingly opposite compulsions to know or control and to admit to chaos or let go sweeps the reader into a maelstrom through a series of linked narrative devices and obliges him to share the creative insanity characteristic of both novelists at their best. Alluding briefly to appropriate analogues to the Apollonian/Dionysian dichotomy in Greek myth and Nietzschean aesthetics and their relevance to prose fiction, this study deals with each novel in turn. By centering on the guiding metaphor of the house, it traces the effects on narrative structure of the clash between knowledge and doubt (represented through Cartesianism and skepticism) and the consequent treatment of time, space and plot. In conclusion, an attempt is made to assess the implications for the novels and for the reader of the ascendancy of the Dionysian element.
Keywords: Samuel Beckett; Robert Pinget; Watt; The Inquisitory; Apollonian; Dionysian; knowledge; doubt